We have to solve : log(4) (x+4) + log(4) 1/(x+1) - 1 = 0

Use the relation log a + log b = log (a*b)

log(4) (x+4) + log(4) 1/(x+1) - 1 = 0

=> log(4) (x + 4) / (x + 1) - 1 = 0

=> log(4) (x + 4) / (x + 1) = 1

=> (x + 4) / (x + 1) = 4

=> x + 4 = 4(x + 1)

=> x + 4 = 4x + 4

=> 3x = 0

=> x = 0

**Log 4 and log 1 exist, so x = 0 is a valid solution.**

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.